Bmi1 marks gastric stem cells located in the isthmus in mice. Issue 2 (20th February 2019) - Yoshioka, Takuto; Fukuda, Akihisa; Araki, Osamu; Ogawa, Satoshi; Hanyu, Yuta; Matsumoto, Yoshihide; Yamaga, Yuichi; Nakanishi, Yuki; Kawada, Kenji; Sakai, Yoshiharu; Chiba, Tsutomu; Seno, Hiroshi
Abstract: In the mammalian stomach, the isthmus has been considered as a stem cell zone. However, various locations and proliferative activities of gastric stem cells have been reported. We focused here on the stem cell marker Bmi1, a polycomb group protein, aiming to elucidate the characteristics of Bmi1‐expressing cells in the stomach and to examine their stem cell potential. We investigated the Bmi1‐expressing cell lineage in Bmi1‐CreERT; Rosa26‐YFP, LacZ or Rosa26‐Confetti mice. We examined the in vivo and ex vivo effects of Bmi1‐expressing cell ablation by using Bmi1‐CreERT; Rosa26‐iDTR mice. The Bmi1 lineage was also traced during regeneration after high‐dose tamoxifen‐, irradiation‐ and acetic acid‐induced mucosal injuries. In the lineage‐tracing experiments using low‐dose tamoxifen, Bmi1‐expressing cells in the isthmus of the gastric antrum and corpus provided progeny bidirectionally, towards both the luminal and basal sides over 6 months. In gastric organoids, Bmi1‐expressing cells also provided progeny. Ablation of Bmi1‐expressing cells resulted in impaired gastric epithelium in both mouse stomach and organoids. After high‐dose tamoxifen‐induced gastric mucosal injury, Bmi1‐expressing cell lineages expanded and fully occupied all gastric glands of the antrum and the corpus within 7 days after tamoxifen injection. After irradiation‐ and acetic acid‐induced gastric mucosal injuries, Bmi1‐expressing cells also contributed to regeneration. In conclusion, Bmi1 is a gastric stem cell marker expressed in the isthmus of the antrum and corpus. Bmi1‐expressing cells have stem cell potentials, both under physiological conditions and during regeneration after gastric mucosal injuries. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.